2021
DOI: 10.1002/pds.5214
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of databases in the Asia‐Pacific for collaborative monitoring of vaccine safety

Abstract: Introduction: Information regarding availability of electronic healthcare databases in the Asia-Pacific region is critical for planning vaccine safety assessments particularly, as COVID-19 vaccines are introduced. This study aimed to identify data sources in the region, potentially suitable for vaccine safety surveillance. This manuscript is endorsed by the International Society for Pharmacoepidemiology (ISPE).Methods: Nineteen countries targeted for database reporting were identified using published country l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Findings from a 2018 survey of electronic data sources suitable for vaccine research in the Asia‐Pacific region indicated that the YRHIP offers relevant vaccine‐specific outcome data 44 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from a 2018 survey of electronic data sources suitable for vaccine research in the Asia‐Pacific region indicated that the YRHIP offers relevant vaccine‐specific outcome data 44 …”
Section: Resultsmentioning
confidence: 99%
“…Expert opinion ACPE in Xi'an provided an important opportunity to leverage insights on the suitability of various RWD sources for vaccine monitoring across the Asia-Pacific region. 44 Discussions organized during the conference between the authors and governmental, academic and industry experts enabled to better understand the RWD landscape and its challenges and opportunities.…”
Section: Resultsmentioning
confidence: 99%
“…7 Administrative claims data, derived from electronic data reported by healthcare providers and insurers for the purposes of reimbursement, provide an affordable and efficient way to monitor vaccine safety. 8 For example, Taiwan's National Health Insurance Research Database (NHIRD) has been utilized for research on influenza vaccination. 9 Recently, researchers of Norway and Denmark also conducted a population-based cohort study on the risk of CVST after administration of ChAdOx1-S (AstraZeneca) vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…One limitation across the types of common epidemiological designs listed above is that there is often variation in vaccine data availability, as well as complexities in data access and data linkage requirements ( Duszynski et al, 2021 ). Generally, there is no one best study design that is superior over the other.…”
Section: Introductionmentioning
confidence: 99%